Effects of English Writing Instruction Using Self-Regulated Strategy Development Model to Enhance Writing Ability of Eleventh Grade Students from Kampong Chheuteal Institute of Technology - ยิน วินดา; ชิโนกุล สุมาลี (An Online Journal of Education, 2019)
This present study investigated the effects of English writing instruction using the Self-Regulated Strategy Development (SRSD) model on enhancing the writing ability of eleventh grade students from Kampong Chheuteal Institute of Technology and explored the students’ opinions toward SRSD instruction. Since this research was conducted during extra class time, the research participants were selected on a voluntary basis. 10 eleventh grade students studying in the Kampong Chheuteal Institute of Technology, in academic year 2017, participated in this study. Both quantitative and qualitative methods were applied. The researcher used an English writing test and semi-structured interview questions to collect data from 15 sessions. Means and standard deviation were calculated and analyzed using a non-parametric design (Wilcoxon Signed Ranks Test) to interpret quantitative data while data obtained from semi-structured interview questions were interpreted by content analysis. The findings revealed that English writing instruction using Self-Regulated Strategy Development enhances the writing ability of eleventh grade students from Kampong Chheuteal Institute of Technology. The average scores of the post-test (M=17.2) was higher than the average scores of the pre-test (M=13.1) at a significant level (p<.05). In accordance with the semi-structured interviews, the students had positive views on learning writing skills via the SRSD model. They requested that the model should be applied in their normal class time as well as in other subject areas. The results of this study could be a great help in guiding Cambodian English teachers on teaching writing skills and improving the English writing ability of EFL students.